Analysis of Character Education Values in Basic Operations of Addition and Subtraction in Elementary School Students’ Finger Arithmetic - Hidayati, Arini Ulfah (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2025)
This study aims to analyze the character values of discipline, hard work, curiosity and self-confidence of students in mathematics learning using finger arithmetic  for elementary school students. This study uses a descriptive qualitative method. The research subjects were five elementary school students and one teacher. Data collection techniques used observation, interviews and documentation. Data were analyzed through three stages, namely: (1) data reduction was carried out by marking observation and interview notes related to the character of discipline, hard work, curiosity and self-confidence, (2) data presentation by presenting it in narrative form and direct quotes per indicator and (3) drawing conclusions by matching data from three data sources. The results of this study indicate that students have possessed these four characters well, this is proven by the results of observations, interviews and documentation (1) discipline is seen in the accuracy of students in submitting assignments, obeying the rules in the finger arithmetic method, (2) hard work is seen in consistent practice, daring to try new things in the finger arithmetic  method, and not hesitating to ask if there is something they don't understand, (3) curiosity is seen in the enthusiasm to ask questions related to the similarities and differences in the finger arithmetic method of addition and subtraction,students' enthusiasm in looking for sources and information and comparing them, and (4) self-confidence is seen in the enthusiasm to appear in front of the class when the teacher gives new questions and daring to demonstrate the finger arithmetic  method.